Amazônia-Criança e a fronteira da vida - Pineda Nebot, Carmen (Sociedad e Infancias, 2020)
Lourenço Mota, M. (2019). Amazônia-Criança e a fronteira da vida. Curitiba: Editora Appris, 295 páginas. ISBN: 978-85.473-1535-1.